Changes in serum proteins and immune response in oreochromis mossambicus induced by aflatoxin B1 - Zacharia, Sherly; Thomas, P C; Paulton, M P (Indian Journal of Fisheries, 2011)
Studies were conducted to evaluate the molecular changes induced by aflatoxin, the most frequently encountered dietary carcinogen in Oreochromismossambicus. Three sub-lethal test doses of aflatoxin B1 incorporated in feed (1.5, 5.0 and 15.0mg/kg feed) were given to the fishes for a period of 30 days and the changes in serum protein profile were resolved through SDS PAGE at regular intervals. Similarly, the changes in immune responses were also studied. The study revealed significant changes in both protein profile and immune response in the experimental fishes compared to the control, indicating that the toxin exerts its effect even at sublethal levels